Effects of nanopowder addition on rheological properties of feedstock for micropowder injection moulding process - Rajabi, Javad; Fayyaz, Abdolali (Penerbit Universiti Kebangsaan Malaysia, 2019)
Micropowder injection moulding (μPIM) is an ideal alternative for miniaturization of parts because of its ability to produce complex micro-geometries at low manufacturing cost. Utilizing bimodal powder mixtures in feedstock can increase packing density and densification of parts fabricated via μPIM. This study investigated the feedstock consists of nano-micro 316L stainless steel powder-and polyethylene glycol-based binder system. The flowability of different feedstocks was evaluated using rheological parameters, including critical powder volume concentration (CPVC), melt viscosity, activation energy, and rheological index. Results showed that mixing nanopowders with micropowders increases CPVC from 67.66 vol.% (pure micropowder) to 78.33 vol.%. The nano-micropowder feedstock showed viscosity below 45 Pa·s and shear rate in the range of 102 s−1 to 105 s−1, which are suitable for the μPIM process. The determined flow index values ranged from 0.25 to 0.76, and the reduced n values at high temperature with the addition of nanopowder indicated a possible increase in shear-thinning behavior. A defect-free microsample was obtained at an injection temperature of 85°C with sintering at 1200°C. Using the nano–micro bimodal powders, the hardness of the obtained samples also increased from 182 HV to 221 HV, with strength of 501 MPa, which is higher than that of the sample obtained with the use of micropowder only (435 MPa).